2023
DOI: 10.4266/acc.2022.01375
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hospital mortality in intensive care unit survivors: a retrospective cohort study

Abstract: Background: Deaths can occur after a patient has survived treatment for a serious illness in an intensive care unit (ICU). Mortality rates after leaving the ICU can be considered indicators of health care quality. This study aims to describe risk factors and mortality of surviving patients discharged from an ICU in a university hospital.Methods: Retrospective cohort study carried out from January 2017 to December 2018. Data on age, sex, length of hospital stay, diagnosis on admission to the ICU, hospital disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…Research has indicated that patients admitted to ICU have a comparatively high death rate, which can range from roughly 15 to 40% ( 20 22 ). Previous studies have mainly focused on ICU-acquired infections ( 23 ) and the forecasting of COVID-19 pneumonia cases and fatalities ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that patients admitted to ICU have a comparatively high death rate, which can range from roughly 15 to 40% ( 20 22 ). Previous studies have mainly focused on ICU-acquired infections ( 23 ) and the forecasting of COVID-19 pneumonia cases and fatalities ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…По данным E Silva LGA et al (2023 г.) отношение шансов (ОШ) летального исхода при наличии инфекции составило для пациентов в ОРИТ 4,305 (95 % доверительный интервал, ДИ: 3,195-5,912, р<0,001) [7]. Анализ 210 исследований (с 1985 по 2021 год) обнаружил тенденцию роста среднего показателя смертности среди пациентов ОРИТ, находившихся на ИВЛ, при этом данные большинства исследований демонстрировали значение летальности, находящееся в пределах от 15 до 30 % [8].…”
Section: введение / Introductionunclassified